2014
DOI: 10.1016/j.jamcollsurg.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy Outcomes Are Superior with the Participation of Residents and Fellows

Abstract: Background Adrenalectomy is a complex procedure performed in many settings, with and without residents and fellows. Patients often ask, "Will trainees be participating in my operation?" and seek reassurance that their care will not be adversely affected. The purpose of this study was to determine the association between trainee participation and adrenalectomy perioperative outcomes. Study Design We performed a cohort study of patients who underwent adrenalectomy from the 2005 to 2011 ACS-NSQIP database. Trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
(20 reference statements)
2
13
1
Order By: Relevance
“…reported that trainee participation is an independent risk factor for longer operative times and both intraoperative and postoperative complications in emergency general procedures . However, reviewing adrenalectomies in the same database, Seib et al found that trainee participation was associated with a lower rate of perioperative complications . Nunobe et al reported that trainees with sufficient experience as an assistant can safely perform laparoscopic gastrectomy .…”
Section: Discussionmentioning
confidence: 99%
“…reported that trainee participation is an independent risk factor for longer operative times and both intraoperative and postoperative complications in emergency general procedures . However, reviewing adrenalectomies in the same database, Seib et al found that trainee participation was associated with a lower rate of perioperative complications . Nunobe et al reported that trainees with sufficient experience as an assistant can safely perform laparoscopic gastrectomy .…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with other studies that have found that trainee participation in surgical procedures is safe. 6,7,20 We found no association between trainee involvement and major perioperative complication among patients undergoing laparoscopic or abdominal hysterectomy and the increased odds of complication among patients undergoing vaginal hysterectomy was small. This finding is consistent with other literature in gynecology that has shown that trainee participation in total laparoscopic hysterectomy for benign disease is ajog.org…”
Section: Commentmentioning
confidence: 55%
“…Many authors report that surgical and center case volumes are predictors of postoperative complications, but others report no such correlation [ 6 9 ]. In our material surgical case volume proved to be an important risk factor for medical complications.…”
Section: Discussionmentioning
confidence: 99%